The reluctant pilgrim : a skeptic's journey into native mysteries - Welsch, Roger L. (Lincoln ; London : University of Nebraska Press, 2015)
"Forty years ago, while paging through a book sent as an unexpected gift from a friend, Roger Welsch came across a curious reference to stones that were round, "like the sun and moon." According to Tatonka-ohitka, Brave Buffalo (Sioux), these stones were sacred. "I make my request of the stones and they are my intercessors," Brave Buffalo explained. Moments later, another friend appeared at Welsch's door bearing yet another unusual gift: a perfectly round white stone found on top of a mesa in Colorado. So began Welsch's lesson from stones, gifts that always presented themselves unexpectedly: during a walk, set aside in an antique store, and in the mail from complete strangers. The Reluctant Pilgrim shares a skeptic's spiritual journey from his Lutheran upbringing to the Native sensibilities of his adoptive families in both the Omaha and Pawnee tribes. Beginning with those round stones, increasing encounters during his life prompted Welsch to confront a new way of learning and teaching as he was drawn inexorably into another world. Confronting mainstream contemporary culture's tendency to dismiss the magical, mystical, and unexplained, Welsch shares his personal experiences and celebrates the fact that even in our scientific world, "Something Is Going On," just beyond our ken. "--
"An honest and revealing description of one skeptic's spiritual journey from his Lutheran upbringing to Native sensibilities"--
Includes bibliographical references.
Print version record.
Keywords: Welsch, Roger L. -- Religion; Spiritual biography -- United States; Anthropologists -- Religious life -- United States; Folklorists -- Religious life -- United States; SOCIAL SCIENCE / Ethnic Studies / Native American Studies; RELIGION / Spirituality; BIOGRAPHY & AUTOBIOGRAPHY / Religious; BODY, MIND & SPIRIT / Inspiration & Personal Growth; BODY, MIND & SPIRIT / Spirituality / General; RELIGION / Christianity / General; RELIGION / Devotional; Electronic books